The Irkutsk cultural project: images of peasants, workers & natives in late imperial Irkutsk province, c.1870-1905 - McGaughey, Aaron (2015)
This thesis explores depictions of established Russian-Siberian peasants, settlers from European Russia, non-agricultural workers, indigenous Buriats and Jews in Irkutsk province during the late imperial period. In particular, it focuses on characterisations of these groups that were created by the Irkutsk 'cultural class' (kul'turnogo klassa) in the late imperial period. The sources it uses are print media such as journals and newspapers produced in or associated with Irkutsk to create a 'microhistorical' study. It is structured around categories of analysis that were used at the time in scientific and literary treatments of lower class peoples, such as social mores, cultural activity, economic function, physiognomy and sexuality. It also studies how these images informed the development of a transformationist culture of government in rural, urban and colonial environments. Using theories of imperial networks and cultural projects borrowed from human and cultural geography and adapting them to an anthropocentric study of Russian colonialism, these debates are situated within the wider context of pan-European, inter-imperial frames of reference. The portrayals of population groups in both domestic and colonial settings that lay within these frameworks rested on common core signs and assumptions found across other pre-war European empires, which made both the frameworks and the images highly portable. This anthropocentric comparative is used to "bring the empire back in", both in recognising the imperial frames of reference within which its culture played out, and also as a means of furthering historiographical analyses that argue against Russian exceptionalism.